The Influence of Compensation and Work Environment on the Performance of Generation Z Employees - Elly Hermawati; Tutik Winarsih (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Generation Z is increasingly dominating the workforce, especially in the Food and Beverage sector such as cafes in Gunung Anyar District, Surabaya, making it important to understand the factors that influence their performance. This study aims to analyze the effect of compensation and work environment on Generation Z employee performance at these cafes. Using quantitative methods with a population of 70 employees, data was collected through questionnaires and observations, then analyzed using multiple linear regression, T-test, F-test, and coefficient of determination with SPSS. The research results show that both compensation and work environment significantly affect Generation Z employee performance at cafes in Gunung Anyar District, Surabaya. The T-test shows significance values below 0.05 for both variables partially, meaning each variable has a positive and significant effect on employee performance. Additionally, the F-test results confirm that compensation and work environment together provide a significant effect on performance with a significance value of 0.000, far below the 0.05 threshold. The coefficient of determination (Adjusted R Square) of 0.604 indicates that 60.4% of employee performance variation can be explained by these two variables, while the remaining 39.6% is influenced by other factors outside this research model. Thus, improving compensation and work environment simultaneously can be an effective strategy to enhance Generation Z performance in the cafe sector. These findings imply that improving compensation and work environment can effectively enhance Generation Z employee performance at cafes in Gunung Anyar District, Surabaya.